CHALLENGES ISLAMIC EDUCATION MANAGEMENT IN THE DIGITAL ERA - Imron Muttaqin (Ta'allum: Jurnal Pendidikan Islam, 2022)
This research aims to explorer the islamic education management in the digital era and the ‎hurdles faced by Islamic education management in adapting to the digital era. A qualitative ‎paradigm and library research design used. The data collection technique performed in this ‎study involves document analysis, encompassing journal articles, proceedings, books, research ‎reports, online news sources, and other relevant materials. The data analysis method employed ‎is content analysis. The findings of present study reveal that the constraints in Islamic ‎education management's response to the digital era primarily revolve around the quality of ‎human resources. These resources have yet to harness digital technology to its fullest ‎potential, resulting in an inability to provide comprehensive digital-based Islamic educational ‎facilities. Furthermore, the competence of Islamic education teachers poses a significant ‎obstacle. Many educators have yet to effectively utilize digital-based learning media in their ‎instructional processes, even as a growing number of students display proficiency in digital ‎technology. Consequently, Islamic education management in the digital era remains ‎comparatively behind general education management.